Effect of 7-step hand washing technique and food sanitation in preventing intestinal parasite infection giardiasis (Giardia lamblia) - Ardiningrum, Nailah Zahrah; Lukiyono, Yauwan Tobing (Environmental and Toxicology Management, 2024)
Over time, Giardia lamblia has become the most dominant causative factor in gastrointestinal diseases in developing countries. The spread of this parasite can also occur through water and food contaminated by sewage and anal sex. In children, Giardiasis transmission usually occurs through fecal-oral transmission or transmission of the disease from feces to the mouth. This research was created to educate readers about the importance of washing hands properly and maintaining food sanitation as well as changing your lifestyle to be cleaner and caring for yourself and those around you in preventing Giardia lamblia infection and exposure to Giardiasis. The research method used is a literature review. References selected from journals, the internet and libraries. Most cases occur through Food Born Disease or food that has been contaminated, in this condition it can occur from various possible causes, it could be due to a lack of hygiene grade on the part of the seller or buyer.